Behavioral Skills Training Program to Improve Personal Safety Skills for a Down Syndrome Adolescent with Mild Intellectual Disability - Kumalasari, Dewi; Kurniawati, Farida (UI Scholars Hub, 2018)
This study investigated the effectiveness of a Behavioral Skills Training program that aimed to improve the personal safety skills of a Down syndrome adolescent with mild intellectual disability. Personal safety was defined as an ability to recognize touch appropriateness, including four self- protective skills; resisting, removing, telling others, and reporting any inappropriate touch experienced. This single-subject design was administered over three days. The results demonstrated that the program was effective at improving the subject’s personal safety skills due to his achieving 97% of the maximum score. The subject was able to master the skills of recognizing, resisting, removing and telling others with a 100% score, while his reporting skill score was 83%. A repetition of this program has been recommended with a specific focus on developing reporting skills. To improve the program’s effectiveness further, in-situ training, training for test administrators, and the provision of reinforcements has been suggested.